ANALYSIS OF THE REAL ESTATE MARKET OF VOLYN REGION - Bochko , O.Yu.; Rosola , U.V. (The actual problems of regional economy development, 2021)
The article reveals the state of the real estate market of Ukraine in general and Volyn region. The relevance of real estate market research is due to the fact that it is characterized by uneven development of its segments, insufficient level of state support and the need for a high level of consumer solvency, which in turn arouses interest of various government agencies, groups and organizations to study this problem. The purpose of writing this article is to investigate the state of the real estate market of Ukraine in general and Volyn region in particular. In the process of writing the article, the authors used the following research methods: inductive, deductive - to collect, process and justify the total number of construction companies operating in the Volyn region; economic analysis and comparison - to analyze the real estate market of Ukraine in general and Volyn region; graphic - to visually reflect the dynamics of changes in the price index in the primary and secondary housing market in Ukraine for 2015-2020, as well as to illustrate the volume of real estate services in the Volyn region; abstract-logical - for theoretical generalizations and conclusions. The dynamics of changes in the price index in the primary and secondary housing market in Ukraine for 2015-2020 is studied, which indicates a constant rate of price growth, especially in 2020. The real estate market of Volyn region is characterized in the following areas: economic characteristics of the industry, analysis of competitors and competitive environment, driving forces, competitive position of major players (strategic groups), key success factors, prospects for the industry and its overall attractiveness. Systematized construction companies operating in the Volyn region. The dynamics of the volume of realized real estate services in Volyn region is given. The influence of factors on the supply and demand of the real estate market is studied. The scientific novelty of the article lies in the novelty of the data obtained in the process of research on the latest trends in the real estate market of Volyn region. Disseminated information will contribute to a more thorough understanding of the current state and development of the real estate market.